Keterkaitan Jangka Panjang dan Jangka Pendek Antara Pertumbuhan Ekonomi dan Tingkat Pengangguran di Provinsi Jambi - Fauzan Aldilah Putra; Yulmardi .; Zulfanetti .; Siti Hodijah; Nurhayani . (JOURNAL OF SHARIA ECONOMICS, 2025)
The study aims to analyze the phenomena between economic growth and the unemployment rate in Jambi Province. both in the short run and the long run. To examine the relationship between economic growth and unemployment in Jambi Province, this research utilizes secondary time-series data covering the period 2004–2024, research data originating from the. Badan Pusat Statistik and Direktoran Jenderal Perimbangan Keuangan. The study employs the Error Correction Model (ECM) approach to identify the dynamic relationship between these variables. Based on the results, in the short run, changes in economic growth have a positive coefficient, suggesting that annual fluctuations in economic growth have not yet had a significant effect on changes in the unemployment rate in Jambi Province. In the long run, however, changes in economic growth show a negative relationship, indicating the presence of a correction mechanism toward long-term equilibrium. This means that short-term disequilibrium in the unemployment rate will be adjusted within one period to restore long-term balance